Variations in performance characteristics of commercial enzyme immunoassay kits for detection of antineutrophil cytoplasmic antibodies: what is the optimal cut off?. Issue 12 (20th April 2005) - Holle, J U; Hellmich, B; Backes, M; Gross, W L; Csernok, E
Abstract : Background: Previous studies have shown considerable variation in diagnostic performance of enzyme linked immunosorbent assays (ELISAs) for measuring antineutrophil cytoplasmic antibodies (ANCA) specific for proteinase 3 (PR3) and myeloperoxidase (MPO). Objective: To analyse the performance characteristics of different commercially available direct ANCA ELISA kits. Methods: ELISA kits for detecting PR3-ANCA and MPO-ANCA from 11 manufacturers were evaluated. Serum samples were taken from patients with Wegener's granulomatosis (15), microscopic polyangiitis (15), other vasculitides (10), and controls (40). Results were compared with data obtained by indirect immunofluorescence (IFT). The diagnostic performance of the tests was analysed and compared by receiver operating characteristic (ROC) curve analysis. Results: Applying the manufacturers' cut off resulted in great variation in sensitivity of the commercial PR3-ANCA kits for diagnosing Wegener's granulomatosis (ranging from 13.3% to 66.7%), and of the MPO-ANCA kits for diagnosing microscopic polyangiitis (ranging from 26.7% to 66.7%). Specificities were relatively constant (from 96.0% to 100%). IFT was superior to all ELISAs (C-ANCA for Wegener's granulomatosis: sensitivity 73.3%, specificity 98%; P-ANCA for microscopic polyangiitis: sensitivity 86.7%, specificity 98%). The sensitivities of PR3-ANCA and MPO-ANCA ELISA kits were increased by lowering the cut off values. This reduced specificity but increased overall diagnostic performance. Conclusions: The low sensitivity of some commercial kits reflects the high cut off levels recommended rather than methodological problems with the assays. Comparative analyses using sera from well characterised patients may help identify optimum cut off levels of commercial ANCA ELISA tests, resulting in better comparability of results among assays from different manufacturers.